Strategic Foresight of Green and Digital Transformation in the Perspective of Best Available Technologies - Kajzer, Špela; Šketa, Anja; Potrč, Melani; Tršinar, Klemen; Brezavšček, Alenka; Bokal, Drago (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The paper addresses the topic of green and digital transformation in light of the EU Strategy on Adaptation to Climate Change by aiming for a climate-resilient EU by 2050. This includes adapting to the unavoidable consequences of climate change, which are already being observed. The green transformation, according to the Seville Process, defines the Best Available Techniques (BAT) for various industries. In the long term, all industrial stakeholders will likely need to meet BAT Reference Document (BREF) standards, ensuring resource efficiency and limiting environmental burdens. The paper presents scientific and professional tools supporting businesses in this transition and assesses education in the field, with a focus on Foresight theory. A key innovation introduced in the paper is the BAT Incubator, which establishes business processes for implementing a developed maturity model. This model evaluates the maturity of business entities concerning components of the green and digital transition. This model, already published and tested on 35 companies across sectors, integrates educational modules from UM (UEZDN) with BREF analysis and business processes. By bridging university expertise with industry needs, the initiative enhances companies’ competitive sustainability while training students to apply these competencies in businesses.